Kajian Geologi Airtanah Menggunakan Survei Investigasi Desain Di Desa Amdasa, Kabupaten Kepulauan Tanimbar - Apalem, Delvia Rimesye; Serang, Rudi; Siahay, Margie Civitaria (JURNAL SIMETRIK, 2025)
Water is a primary human need that must be met, but overtime the rate of population growth, the need for water in Amdasa Village, Wertamrian District, Tanimbar Islands Regency is decreasing. Increased water use is sometimes not accompanied by the management of new water sources due to the lack of information about the potential of groundwater sources. Geoelectric surveys will provide potential difference values, current strength, and rock specific resistance values. The value of the rock's specific gravity is then further processed to obtain the value of the specific gravity of each rock layer. The research location has good aquifer potential indicated by the discovery of aquifer layers at shallow depths from the surface of 6 meters and up to 13 meters with various aquifer thicknesses and groundwater well design with a drilling depth of ± 16 meters for points 01 and 03. Keywords: Groundwater, geoelectric method, potential difference, aquifer